2011
DOI: 10.1152/jn.00736.2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of the vesicular transporter VGLUT3 in retrograde release of glutamate by cerebellar Purkinje cells

Abstract: In the cerebellum, retrograde release of glutamate (Glu) by Purkinje cells (PCs) participates in the control of presynaptic neurotransmitter release responsible for the late component of depolarization-induced suppression of excitation (DSE), as well as for depolarization-induced potentiation of inhibition (DPI). It might also participate in the depolarization-induced slow current (DISC) in PCs, although this contribution was later challenged. We also know that both DPI and DISC are soluble N-ethylmaleimide-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Interestingly, VGLUT3 has the ability to signal retrogradely [ 5 , 70 ]. Crepel et al showed that cerebellar principle cells utilise Glu released from VGLUT3 containing vesicles to retrogradely signal and regulate incoming signals.…”
Section: Characterisation Of Vglut3mentioning
confidence: 99%
“…Interestingly, VGLUT3 has the ability to signal retrogradely [ 5 , 70 ]. Crepel et al showed that cerebellar principle cells utilise Glu released from VGLUT3 containing vesicles to retrogradely signal and regulate incoming signals.…”
Section: Characterisation Of Vglut3mentioning
confidence: 99%
“…These results are all consistent with higher CP-AMPARs in RMTg in the saline and high-avoider groups compared with low avoiders. However, those experiments used electrically evoked eEPSCs, whose amplitudes could be confounded by known effects on presynaptic release of the many postsynaptic depolarization steps used in our R.I. tests (Kreitzer and Regehr, 2001;Wilson and Nicoll, 2001;Ohno-Shosaku et al, 2002;Kreitzer and Malenka, 2005;Crepel and Daniel, 2007;Crépel et al, 2011). Hence, to control for possible presynaptic differences in electrically evoked glutamate, we repeated the R.I. tests using photolytically uncaged glutamate while blocking presynaptic transmission with TTX.…”
Section: Cocaine-avoiding Rats Exhibit Enhanced Excitability Of Vtapr...mentioning
confidence: 99%